A novel bis-component AIE smart gel with high selectivity and sensitivity to detect CN−, Fe3+ and H2PO4−. Issue 31 (10th July 2019) - Gong, Guan-Fei; Chen, Yan-Yan; Zhang, You-Ming; Fan, Yan-Qing; Zhou, Qi; Yang, Hai-Long; Zhang, Qin-Peng; Yao, Hong; Wei, Tai-Bao; Lin, Qi
Abstract : A novel bis-component AIE smart gelTG could be used for high efficiency and sensitive ions (CN −, Fe 3+ and H2 PO4 − ) detection and separation. The LODs ofTG for CN −, Fe 3+ and H2 PO4 − are in the range of 4.93 × 10 −9 –7.80 × 10 −8 M. Abstract : A novel bis-component AIE-gelTG was facilely constructed from two "easy-to-synthesize" tripodal gelators by a simple host–guest self-assembly process. Interestingly, theTG shows strong aggregation-induced emission (AIE) and could be used for highly efficient and sensitive detection and separation of ions (CN −, Fe 3+ and H2 PO4 − ). The LODs (limits of lowest detection) ofTG for CN −, Fe 3+ and H2 PO4 − are in the range of 4.93 × 10 −9 –7.80 × 10 −8 M. Meanwhile, the xerogel ofTG could adsorb and separate Fe 3+ from aqueous solutions, and the adsorption rate is 96%. In addition, a thin film based on theTG could act as a convenient test kit for the detection of CN − and Fe 3+ . What is more, theTG-Fe film could not only be used as an erasable secure fluorescent display material, but also as a convenient reversible H2 PO4 − test kit.